TINJAUAN LITERATUR: EFEKTIVITAS PENGGUNAAN MEDIA VIDEO ANIMASI DALAM PROSES PEMBELAJARAN PENDIDIKAN VOKASIONAL - Idah Faridah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Vocational learning requires innovative approaches to increase its effectiveness in today's digital era. One interesting approach is the use of animated video media in the learning process. This article presents a literature review on the effectiveness of using animated video media in the context of vocational education. This literature review aims to explore how the use of animated video media can improve students' understanding of vocational subject matter, motivate learning, and increase student engagement in the learning process. The practical implications of using this media in vocational learning will also be discussed